2017
DOI: 10.17221/36/2016-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Decision support system to find a skid trail network for extracting marked trees

Abstract: Parsakhoo A., Mostafa M., Shataee S., Lotfalian M. (2017): Decision support system to find a skid trail network for extracting marked trees. J. For. Sci., 63: 62-69.Careful planning of skid trails as wood extraction routes in forests is an ongoing task and necessary for minimizing the environmental damage. The main objective of this study is to find skid trails to extract marked trees from stand sites to landing sites using a GIS-based decision support system (DSS) and network analysis techniques, where enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Imani et al [38] compared the forest roads variants obtained by Dijkstra's method and the traditional method and found that by using the first method they obtained lower length and costs for 55% and 65%. Parsakhoo et al [39] obtained shorter routes by 12.03% in average, by using Dijkstra's algorithm. In this investigation, by using the method of the shortest route, longer routes were obtained in relation to the existing network that is laid in a traditional way.…”
Section: Variant IIImentioning
confidence: 99%
“…Imani et al [38] compared the forest roads variants obtained by Dijkstra's method and the traditional method and found that by using the first method they obtained lower length and costs for 55% and 65%. Parsakhoo et al [39] obtained shorter routes by 12.03% in average, by using Dijkstra's algorithm. In this investigation, by using the method of the shortest route, longer routes were obtained in relation to the existing network that is laid in a traditional way.…”
Section: Variant IIImentioning
confidence: 99%
“…Several previous authors have considered harvesting at individual tree levels, but their studies were focused on stand management rather than landscape restoration [13][14][15][16][17][18]. The studies by Pukkala et al [15], Pukkala and Miina [16], Vauhkonen and Pukkala [17], and Wing et al [18] were focused on the selection of individual trees to be thinned using either a deterministic or a heuristic algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the problem size, the trees accessible to each landing were limited. The tree level problem addressed by Parsakhoo et al [13] in the Hyrcanian forests of Iran also sought to minimize skid trail length to avoid environmental impacts using multi-objective criteria analysis and network programming but did not consider landing costs. A tree-level solution was proposed by Contreras and Chung [19] to reduce the crown fire potential in stands dominated by Douglas fir (Pseudotsuga menziesii (Mirb) Franco), ponderosa pine (Pinus ponderosa Dougl.…”
Section: Introductionmentioning
confidence: 99%